A Review of U.S. Policy Guidance and Legislation on Restraint and Seclusion in Schools: Considerations for Improvement - Laura Kern; Heather Peshak George
Restraint and seclusion (R/S) are practices employed by schools to address severe student behavior. Although the use of R/S has been shown to have harmful impact for students, staff, and schools, there is no federal law that addresses its use in schools. A lack of a universal approach leaves each state to determine its own legislation and policy. The current study seeks to extend previous research efforts on state policy guidance and legislation reviews on the use of R/S by reporting on key similarities and differences across states policy guidance and legislation. Specifically, policy guidance and legislation on the school use of R/S are reviewed from the U.S. states and territories, including Washington, D.C.; Puerto Rico; Guam; and the Virgin Islands. Most states and territories were found to have either legislation or policy guidance on the use of R/S in schools. However, there are many differences across the states, including on its use and reporting for students with disabilities. Findings are also compared with the proposed federal bill Keeping All Students Safe Act. Finally, given the lack of passage of the federal law, highlights and recommendations are provided for state leaders on considerations for improvement as R/S remains a state regulated educational issue.